THE INFLUENCE OF PSYCHOLOGICAL CLIMATE AND CHANGE-ORIENTED LEADERSHIP ON EMPLOYEE PERFORMANCE OF PT. WASKITA KARYA (PERSERO) Tbk - Ali Efendi Siburian; Prihatin Lumbanraja; Sugih Arto Pujongkoro (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The aim of this research is to determine and analyze the influence of the psychological climate and change-oriented leadership on the performance of PT. Waskita Karya (Persero), Tbk. employees. The approach used in this research is an associative approach. The population in this research are 200 employees at PT. Waskita Karya, North Sumatra Province, and the sample used in this research were 119 people using Purposive Sampling. Data collection techniques in this study used a questionnaire. The data analysis technique in this study used Multiple Linear Regression, Classic Assumption Test, t-test, and F-test, and Coefficient of Determination. Data processing in this study used the SPSS software program (version 25.00). The results of this research are that there is an influence of psychological climate and change-oriented leadership on the performance of PT. Waskita Karya (Persero), Tbk. employees.